On an inequality of smoothing - Paulauskas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Паулаускас. О неравенстве сглаживания V. Paulauskas. Apie suglodinimo nelygybę